Deflection-Based Numerical Evaluation of Steel, Bamboo Fibre, and Carbon Fibre Polymer Reinforced Portal Frame - S.O Odeyemi; M.A Olawale; M.O Adisa; O.D Atoyebi; Z.T Giwa (Journal of Building Materials and Structures)
Reinforced concrete, a flexible building material, enjoys worldwide acceptance. Yet, its environmental footprint, especially regarding steel production, is substantial. The extensive mining of iron ore contributes to global warming, prompting the quest for greener alternatives. Bamboo fibre and carbon fibre were employed in sustainable industrial and construction practices to fulfill tensile requirements in reinforced concrete, effectively managing lateral loads on structural elements. This study aims to compare numerically the deflection resistance of portal frames reinforced with steel, bamboo fibre, and carbon fibre polymers using Abaqus version 6.14. The replacement of steel with carbon fibre within the portal frame exhibited comparable effectiveness to that of utilizing steel, whereas the introduction of bamboo fibre was observed to yield relatively diminished efficacy. However, differences between the results for steel, bamboo fibre, and carbon fibre are minimal, and carbon fibre performs similarly to steel. The maximum lateral movement values are 2.43 mm for steel, 2.68 mm for bamboo fibre, and 2.39 mm for carbon fibre.